2010
DOI: 10.1103/physrevb.81.125409
|View full text |Cite
|
Sign up to set email alerts
|

Strain effect on quantum conductance of graphene nanoribbons from maximally localized Wannier functions

Abstract: Density functional study of strain effects on the electronic band structure and transport properties of the graphene nanoribbons (GNR) is presented. We apply a uniaxial strain (ε) in the x (nearest-neighbor) and y (second nearest-neighbor) directions, related to the deformation of zigzag and armchair edge GNRs (AGNR and ZGNR), respectively. We calculate the quantum conductance and band structures of the GNR using the Wannier function in a strain range from −8% to +8% (minus and plus signs show compression and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…It was shown that below a threshold value (which may exceed 20%, depending on direction), uniaxial strain will not open an energy gap for infinite graphene sheets, but just cause the Fermi crossing to move away from the K point [26,27,30,31]. In the case of GNRs, uniaxial strain has little influence on the band structure of zigzag GNRs (ZGNRs), while the energy gap of armchair GNRs (AGNRs) is modified in a periodic way with a zigzag pattern [21,25,29,32]. Accordingly, AGNRs and ZGNRs possess distinct charge transport properties under strain [30,[32][33][34], e.g., ZGNRs remain robust against high uniaxial strain [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that below a threshold value (which may exceed 20%, depending on direction), uniaxial strain will not open an energy gap for infinite graphene sheets, but just cause the Fermi crossing to move away from the K point [26,27,30,31]. In the case of GNRs, uniaxial strain has little influence on the band structure of zigzag GNRs (ZGNRs), while the energy gap of armchair GNRs (AGNRs) is modified in a periodic way with a zigzag pattern [21,25,29,32]. Accordingly, AGNRs and ZGNRs possess distinct charge transport properties under strain [30,[32][33][34], e.g., ZGNRs remain robust against high uniaxial strain [33].…”
Section: Introductionmentioning
confidence: 99%
“…Scanning tunneling microscopy (STM) studies on graphene have indeed revealed a correlation between local strain and tunneling conductance [20]. Theoretically, both the tight-binding (TB) model and ab initio approaches have been widely adopted to investigate the effect of strain on the band structure of graphene and graphene nanoribbons (GNRs) [14,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It was shown that below a threshold value (which may exceed 20%, depending on direction), uniaxial strain will not open an energy gap for infinite graphene sheets, but just cause the Fermi crossing to move away from the K point [26,27,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] In contrast, theoretical studies advise a GNR could have sizable bandgap changes under uniaxial strain, [ 22 ] which could be useful for implementing graphene technology. Uniaxial strain modulates the bandgap of GNRs by shifting the Dirac point relative to the allowed wavevector lines ( k -lines) in armchair GNRs, and by modifying the magnitude of spin polarization at the edges in zigzag GNRs.…”
Section: Doi: 101002/adma201403750mentioning
confidence: 96%
“…[ 22,23 ] Both ab initio calculations and tightbinding modeling show no bandgap opening for 2D graphene [+] These authors contributed equally to this work.…”
Section: Doi: 101002/adma201403750mentioning
confidence: 99%
“…Particularly, strain studies on graphene nanoribbons are gaining much attention as the control of their mechanical deformation could allow the creation of novel devices for energy harvesting [83][84][85][86] . There exist many reports on the electronic structure modification via strain engineering of simulated systems of different edge type, edge decoration, shape, and width [46][47][48][49][50][87][88][89][90][91][92][93][94][95][96] . Among those researchers, some outstand by including analyses of the current-voltage characteristics 43,44,92,97,98 .…”
mentioning
confidence: 99%